Rydberg series of dark excitons and the conduction band spin-orbit splitting in monolayer WSe2 - Kapuscinski, Piotr; Delhomme, Alex; Václavková, Diana; Slobodeniuk, Artur; Grzeszczyk, Magdalena; Bartoš, Miroslav; Watanabe, Kenji; Taniguchi, Takashi; Faugeras, Clément; Potemski, Marek (NATURE PORTFOLIO, 2021)
Strong Coulomb correlations together with multi-valley electronic bands in the presence of spin-orbit interaction are at the heart of studies of the rich physics of excitons in monolayers of transition metal dichalcogenides (TMD). Those archetypes of two-dimensional systems promise a design of new optoelectronic devices. In intrinsic TMD monolayers the basic, intravalley excitons, are formed by a hole from the top of the valence band and an electron either from the lower or upper spin-orbit-split conduction band subbands: one of these excitons is optically active, the second one is dark, although possibly observed under special conditions. Here we demonstrate the s-series of Rydberg dark exciton states in tungsten diselenide monolayer, which appears in addition to a conventional bright exciton series in photoluminescence spectra measured in high in-plane magnetic fields. The comparison of energy ladders of bright and dark Rydberg excitons is shown to be a method to experimentally evaluate one of the missing band parameters in TMD monolayers: the amplitude of the spin-orbit splitting of the conduction band. Excitonic physics dominates the optical response of semiconductor monolayers but single particle band structure parameters are hard to probe experimentally. Here, spin-orbit splitting in the conduction band of monolayer WSe2 is revealed by the identification of the Rydberg series of dark excitons.

Strong Coulomb correlations together with multi-valley electronic bands in the presence of spin-orbit interaction are at the heart of studies of the rich physics of excitons in monolayers of transition metal dichalcogenides (TMD). Those archetypes of two-dimensional systems promise a design of new optoelectronic devices. In intrinsic TMD monolayers the basic, intravalley excitons, are formed by a hole from the top of the valence band and an electron either from the lower or upper spin-orbit-split conduction band subbands: one of these excitons is optically active, the second one is dark, although possibly observed under special conditions. Here we demonstrate the s-series of Rydberg dark exciton states in tungsten diselenide monolayer, which appears in addition to a conventional bright exciton series in photoluminescence spectra measured in high in-plane magnetic fields. The comparison of energy ladders of bright and dark Rydberg excitons is shown to be a method to experimentally evaluate one of the missing band parameters in TMD monolayers: the amplitude of the spin-orbit splitting of the conduction band. Excitonic physics dominates the optical response of semiconductor monolayers but single particle band structure parameters are hard to probe experimentally. Here, spin-orbit splitting in the conduction band of monolayer WSe2 is revealed by the identification of the Rydberg series of dark excitons.
Rydberg series of dark excitons and the conduction band spin-orbit splitting in monolayer WSe2
Keywords: PHOTOLUMINESCENCE; PHOTOLUMINESCENCE